Möglichkeiten und Grenzen der textgrammatischen Analyse - Greule, Albrecht (Studia Germanica Posnaniensia, 2018)
In a text analysis of H. von Kleist's parable "Mutterliebe" the author exemplifies the basic concepts, categories and principles of modern discourse analysis, such as verbal and pragmatic coherence, referential recurrence, isotopy and classeme. Another text analysis, that of the poem "München" by G. Keller, shows that limits are set to the presented text-grammatical approach.